Strategi Guru Akidah Akhlak dalam Menanamkan Karakter pada Peserta Didik di MTs Yaspend Muslim Pematang Tengah - Nurul Syahputri; Hayatun Sabariah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Research has been carried out on the Strategy of Akhlak Teachers in Instilling Character in Students at MTs Yaspend Muslim Pematang Tengah. This research is a qualitative research using a descriptive qualitative approach. This research only tries to reveal or describe the facts that exist in MTs Yaspend Muslim Pematang Tengah. The researcher acts as a key instrument. The data sources used are secondary and primary data sources. The approaches used are: a) pedagogic approach, b) psychological approach, and c) social approach. The results obtained include: Objective conditions regarding the character of students at MTs Yaspend Muslim Pematang Tengah in general, students have good character. The visible characters shown by students in the MTs Yaspend Muslim Pematang Tengah environment can be concluded as; Students tend to be obedient, polite to all teachers and to fellow students, disciplined, calm and earnest and always maintain harmony and intimacy with others. b) There are several supporting and inhibiting factors for teachers of moral aqidah in instilling character in students at MTs Yaspend Muslim Pematang Tengah, and c) Teachers providing guidance through lectures (at school and at home), it is recommended/required to read a lot of things related to religion ( relating to the formation of character for students with problems continue to be given direction so as not to repeat the mistakes they have made, students with problems are handed over to the BK teacher (BP teacher) for guidance.